PENGARUH CAPITAL ADEQUACY RATIO (CAR), LOAN AT RISK (LAR) DAN SITUASI PANDEMI TERHADAP PROFITABILITAS DI PERUSAHAAN SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2018 DAN 2020 - Arial Batitusta; Yulius Christiawan (Business Accounting Review, 2021)
This study aims to test whether the Capital Adequacy Ratio (CAR), Loan at Risk (LAR) and the Pandemic Situation have an effect on profitability. This research was conducted on 42 companies in the banking sector listed on the Indonesia Stock Exchange (IDX) in 2018 and 2020. The hypothesis testing in this study uses a panel data regression model. The results of this study found that the variables Capital Adequacy Ratio and Loan at Risk have a significant effect on profitability. In addition, the Pandemic Situation variable has an insignificant effect on profitability. The results of this study can be used by bank management as additional information in making decisions in banking